Performance improvement of double-slope solar still using locally sourced sand, coupled with glass cooling integration - Ahmad A. Tareemi; Swellam W. Sharshir (Results in Engineering)
The performance of traditional solar stills (SSs) is often hindered by inefficiencies and low rates of freshwater production. This study proposes a novel approach to enhance the performance of double slope SSs by incorporating environmentally friendly and recovery-based features. Minerals derived from black sand are suggested as sustainable alternatives to synthetic nanofluids and conventional heat storage materials. Four configurations of SSs are examined: one with natural black sand, one with black sand and a glass cover cooling, one utilizing minerals from black sand for sensible heat storage, and a final configuration combining these minerals with glass cooling. A comprehensive analysis is conducted to evaluate the energy, exergy, cost, and environmental performance against a conventional SS. The findings indicate significant improvements in efficiency and productivity. The use of natural black sand increased freshwater production by 35.45 %, while thermal and exergy efficiencies improved by 35 % and 58 %, respectively. The application of glass cooling resulted in a 59.46 % increase in freshwater production, alongside a 59 % enhancement in thermal efficiency and a 75 % improvement in exergy efficiency. When black sand minerals were employed, productivity rose by 63.6 %, with thermal efficiency increasing by 62 % and exergy efficiency improving by 104 %. The combination of these minerals with glass cooling led to a remarkable 80.96 % increase in productivity, with thermal efficiency reaching 52.44 % (81 % improvement) and exergy efficiency climbing to 3.31 % (102 % enhancement). The analysis underscores the sustainability of this system, as it reduces the cost of freshwater by 43 % and decreases CO2 emissions by 2.10 tons.